Pengaruh Pengalaman Merek terhadap Niat Membeli Kembali: Peran Mediasi Kepuasan Pelanggan dan Suasana Toko pada Konsumen Generasi Z - Praditha Rizky Amalia; Mohamad Rifqy Roosdhani (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
This study examines the effect of brand experience on repurchase intention with customer satisfaction and store atmosphere as mediating variables among Generation Z consumers at X Coffee and Eatery. A quantitative approach was employed using a survey of 139 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that brand experience has a positive and significant effect on repurchase intention, customer satisfaction, and store atmosphere. In addition, store atmosphere positively affects repurchase intention and significantly mediates the relationship between brand experience and repurchase intention. Conversely, customer satisfaction neither affects repurchase intention nor mediates the relationship between brand experience and repurchase intention. These findings extend the application of Expectation Confirmation Theory (ECT) in the coffee shop industry by highlighting the importance of brand experience and store atmosphere in encouraging repurchase intention among Generation Z consumers. The findings also provide practical insights for managers to strengthen brand experience and optimize store atmosphere to encourage repeat purchases.